Recreational 'mud fever': Leptospira interrogans induced diffuse alveolar hemorrhage and severe acute respiratory distress syndrome in a U.S. Navy seaman following 'mud-run' in Hawaii. (2019) - Schmalzle, Sarah A; Tabatabai, Ali; Mazzeffi, Michael; Matta, Ann; Hollis, Allison; Zubrow, Marc; Rajagopal, Keshava; Thom, Kerri; Scalea, Thomas
Abstract: A 23-year-old man with a viral-like prodrome developed sudden severe dyspnea and was found to have renal failure, anemia, shock, and diffuse alveolar hemorrhage with acute respiratory distress syndrome, requiring emergent endotracheal intubation and extracorporeal membrane oxygenation (ECMO). Travel and exposure history from peripheral sources revealed that the patient had participated in a 'mud-run' in Hawaii two weeks prior to symptom onset. The patient was subsequently diagnosed with leptospirosis and treated with ceftriaxone and doxycycline. He was discharged on hospital day 13 with full recovery. Leptospirosis is associated with exposure to water, soil, or other matter contaminated with urine of carrier animals. It has been associated with a multitude of activities over time; most recently recreational water-based activities including 'mud-runs' in endemic areas have been added to the list of routes of exposure. This case underscores the importance of obtaining a thorough epidemiological exposure and travel history and being aware of areas of endemicity for life-threatening infections. Additionally, to our knowledge this is the second case of a patient in the United States treated with ECMO for leptospirosis induced pulmonary hemorrhage.